Information security in data loss prevention: a systematic review - Rojas Valiente, Mishael Jeanpier (2023)
Currently, there is a notable increase in data loss cases, which can result in great economic losses for organizations. Data loss is a frequent problem in different information systems and can occur due to various reasons, such as hardware failure, human error, malicious attack, and natural disaster, among others. This systematic review aims to identify the impact of Information Security Management on the prevention of data loss. To carry out this research, the PRISMA methodology was used and searches were carried out in 6 databases: Scopus, Scielo, Alicia, Google Scholar, Science Direct and Redalyc. A total of 59 documents were found, and applying the exclusion and inclusion criteria, 9 documents were chosen for analysis. Of the selected documents, it was found that the massive increase in information stored in database systems has led to an increase in security breach attempts by outsiders. This research argues that organizations must implement adequate information security management to protect their data and the privacy of their customers. It is concluded that a suitable Information Security Management helps to reduce and prevent data loss by identifying and correcting vulnerabilities, which has an improvement relationship in the protection of data stored by organizations.